Innovation and Education - Bulent Tarman (Research in Social Sciences and Technology- OpenED Network, 2016)
We are living in a world that is changing rapidly and becoming more globalized. Especially the changes in the areas of science, technology and economy are becoming effective in the areas like education and health that are closely related to human life. We are experiencing a quick process named